2020
DOI: 10.1016/j.annonc.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Lurbinectedin as second- or third-line palliative therapy in malignant pleural mesothelioma: an international, multi-centre, single-arm, phase II trial (SAKK 17/16)

Abstract: Background: Systemic second-and third-line therapies for malignant pleural mesothelioma (MPM) result in a median progression-free survival (mPFS) of <2 months and median overall survival (mOS) of 6e9 months. Lurbinectedin binds to the DNA of the regulatory region while inhibiting tumour-associated macrophage transcription. In early trials, encouraging outcomes occurred in patients (pts) with MPM treated with lurbinectedin. We aimed to generate lurbinectedin efficacy and safety data among pts with progressive M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…As a consequence of DNA damage, replication arrest, and induction of apoptosis, we propose that lurbinectedin impairs the tumorigenic potential of MPM cells, and our results provide support to the clinical data recently reported in a multicentric phase II trial in second-or third-line palliative therapy [37]. Speculatively, considering the high anti-proliferative effect, if the results of the present study will be confirmed in MPM PDXs, lurbinectedin could be potentially investigated in the front line setting, for instance for a short pre-operative treatment in the early stages of MPM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a consequence of DNA damage, replication arrest, and induction of apoptosis, we propose that lurbinectedin impairs the tumorigenic potential of MPM cells, and our results provide support to the clinical data recently reported in a multicentric phase II trial in second-or third-line palliative therapy [37]. Speculatively, considering the high anti-proliferative effect, if the results of the present study will be confirmed in MPM PDXs, lurbinectedin could be potentially investigated in the front line setting, for instance for a short pre-operative treatment in the early stages of MPM.…”
Section: Discussionsupporting
confidence: 90%
“…Lurbinectedin (PM01183) is a marine-derived anticancer drug that exerts a potent antitumor activity in different cancer cell lines and xenografts models and is currently under clinical evaluation in several tumor types [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Recently, the FDA has released a conditional approval for lurbinectedin for the treatment of second-line metastatic small cell lung cancer patients [ 36 ] while promising antitumor activity has been reported in MPM patients in second- and third-line [ 37 ]. However, there are no data available on the role of lurbinectedin as monotherapy or in combination in the first-line treatment of MPM.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ATREUS trial, where this drug was administered as second line therapy in epithelioid MPM and as a first or second line in non-epithelioid subtype, showed poor efficacy of trabectedin and high liver toxicity that did not justify further use of this drug ( 157 ). However, lurbinectedin, an analogue of trabectedin, has shown promising results in a phase II clinical trial, where it was administered as a second or third line therapy in MPM patients ( 133 ) ( Table 2 ). Lurbinectedin was efficacious independently on the MPM histotype and previous treatment.…”
Section: Novel Molecular Targets For Therapeutic Strategiesmentioning
confidence: 99%
“…As the efficacy of first-line chemotherapy remains poor, numerous studies have been carried out to improve the outcomes but without satisfactory results. A recent phase II trial of lurbinectedin in relapsed pleural mesothelioma showed a progression-free survival (PFS) rate of 52.4% at 12 months (7). Here, we report on good tolerability and efficacy of lurbinectedin in two patients with heavily pretreated DMPM.…”
Section: Introductionmentioning
confidence: 81%
“…In June 2020, based on the results from a phase II trial (study B-005; NCT02454972), the US Food and Drug Administration (FDA) granted accelerated approval to lurbinectedin for adult patients with metastatic small-cell lung cancer with disease progression on or after platinum-based chemotherapy (12). The Swiss Group for Clinical Cancer Research (SAKK) 17/16 trial, a phase II singlearm study, was designed to evaluate lurbinectedin efficacy and safety in patients with progressive malignant pleural mesothelioma (7). The primary endpoint of PFS at 12 weeks was met by 52.4% of patients; median PFS and median overall survival were 4.1 months and 11.1 months, respectively.…”
Section: Discussionmentioning
confidence: 99%